2017
DOI: 10.3892/etm.2017.5115
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment of diabetic nephropathy with alprostadil and calcium dobesilate

Abstract: This study investigated the effects of alprostadil combined with calcium dobesilate on the treatment of diabetic nephropathy. We recruited 80 patients with diabetic nephropathy, who were randomly divided into experimental (n=40) and control (n=40) groups. Patients received high-quality low-protein diabetic diet intervention and subcutaneous injection of insulin to adjust blood glucose, combined with antihypertensive, antiplatelet drugs, and other comprehensive treatments. The control group received alprostadil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…SCr, BUN, and serum 2 -MG are common biochemical markers reflecting glomerular damage. 24 We found that there were no significant difference in SCr, BUN, and serum 2 -MG among the groups, which was similar to the results reported by Abdelraouf et al, 21 who found no significant fluctuation in SCr in any of the rats treated with PMB at 5 mg/kg body weight daily for up to 10 days. These findings indicated that PMB administered at a lower dose such as 4 or 5 mg/kg body weight daily may not result in injury to renal glomeruli.…”
Section: Discussionsupporting
confidence: 91%
“…SCr, BUN, and serum 2 -MG are common biochemical markers reflecting glomerular damage. 24 We found that there were no significant difference in SCr, BUN, and serum 2 -MG among the groups, which was similar to the results reported by Abdelraouf et al, 21 who found no significant fluctuation in SCr in any of the rats treated with PMB at 5 mg/kg body weight daily for up to 10 days. These findings indicated that PMB administered at a lower dose such as 4 or 5 mg/kg body weight daily may not result in injury to renal glomeruli.…”
Section: Discussionsupporting
confidence: 91%
“…Alprostadil can protect the microcirculation and inhibit inflammatory responses, and, as is known, have antiinflammatory and anti-apoptotic effects on the myocardium [24][25][26][27]. We found that alprostadil reversed the decline of cell activity, reduced LDH and troponin levels, and down-regulated the expression of inflammatory factors in H9c2 cells treated with LPS, which suggests that alprostadil had a protective effect on myocardial cells.…”
Section: Discussionsupporting
confidence: 62%
“…Clinical research has demonstrated that alprostadil can reduce the expression of inflammatory factors such as myeloperoxidase (MPO), TNF-α, and IL-6 in the treatment of ischemia reperfusion injury, contrast nephropathy, and diabetic nephropathy etc. [24][25][26][27]. Furthermore, PGE1 improved the myocardial microcirculation and alleviated apoptosis of myocardial cells [28,29].…”
mentioning
confidence: 99%
“…CaD is applied for the treatment of diabetic microvascular diseases, especially for diabetic retinopathy because of its angioprotective properties (Suschek et al, 1997; Brunet et al, 1998; Brunet et al, 1998; Leal et al, 2010). Clinical studies have noted that alprostadil combined with CaD is widely applied for the treatment of renal disease (Qin et al, 2017), and CaD has been confirmed to be effective in maintaining the construction of the vascular endothelium and enhancing renal function (John and Ning, 2016). However, the specific mechanism is not yet clear.…”
Section: Discussionmentioning
confidence: 99%